Problematika Hukum Keluarga: Antara Fenomena dan Paradigma Kitab Klasik - Jaenal Aripin (Universitas Islam Negeri Jakarta, 2012)
Abstract: Problems with Family Law: The Phenomena and the Paradigm of Classical Texts. There are many factors that can trigger the emergence of family problems. One factor that is especially influential is diminished adherence to religious values, in which husbands, wives and children forgo using these values as the foundations upon which to live. If that is the cause of family problems, returning to religious values can provide one way of solving them. But these values aren’t problem-free either, given that religious texts, especially classical religious texts, seem misogynistic and too discriminatory towards women, limiting their roles only to inside domestic matters. Because of these problems, this article argues that creating a harmonious life between husband and wife must be guided by principles promoting equal rights and valuing each spouse’s role equally.Keywords: family law, religious value, classical textAbstrak: Problematika Hukum Keluarga: Antara Fenomena dan Paradigma Kitab Klasik. Banyak faktor yang menyebabkan munculnya masalah di dalam keluarga. Salah satu yang kuat pengaruhnya adalah karena lunturnya pengamalan nilai-nilai agama, yang tidak lagi dijadikan landasan dalam berpijak, baik oleh suami, isteri maupun anak. Karena itu, kembali kepada nilai-nilai agama menjadi salah satu solusi tawarannya. Namun bukan tanpa masalah, mengingat teks-teks keagamaan khususnya klasik, kadang terkesan mesoginis dan terlalu mendeskriminasi kaum perempuan dan membatasi peran mereka hanya dalam urusan domestik. Karenanya, prinsip-prinsip yang mengedepankan persamaan hak dan saling menghargai peran, harus dipedomani guna menciptakan kehidupan harmonis antara suami isteri.Kata Kunci: hukum keluarga, nilai keagamaan, teks klasikDOI: 10.15408/ajis.v12i1.962